Nilai-Nilai Pendidikan Akhlak dalam Film Budi Pekerti Karya Wregas Bhanuteja - Nurul Khofifah; Dudi, Asep; Hayati, Fitroh (UNISBA Press, 2024)
Abstract. Moral education is one of the key educational components influencing national progress as it plays a crucial role in shaping an individual's character. Education is an essential requirement for human life that must be fulfilled throughout one's lifetime. Without education, it would be impossible for humans to advance rapidly in life. This guidance counselor often provides reflections to his students, which have a positive impact on them. The moral values conveyed in the film